THE PRODUCTION PROCESS ACTIVITIES, DISTRIBUTION NETWORK AND POTENTIAL CONSUMPTION OF LOCAL FOOD - Lufita Widiana (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
In the essence to meet the economic needs, there must be goods and services. The goods and services as a means of satisfying the needs that must be held or made (in production). After the goods and services are created or manufactured, these goods and services must be distributed to the community as users or consumers of the goods and services.